91-days-old piglets recognize and remember an old aversive handling - Sommavilla, R.F. (2014)
The aim of this study was to perceive if piglets can recognize their aversive handling and if they can remember this aversive handling after three weeks with no contact with this person. For this, 16 piglets received an aversive treatment during their first 70 days of life: between day 1 and 28 this treatment was applied daily and, from day 29 to day 70, during alternate days. This aversive treatment was made by the same person (AH), a woman wearing orange coveralls and black boots. For the aversive treatment, AH was noisy, moved harshly and unpredictably and shouted frequently during routine cleaning of facilities and animal handling. After day 70 they received a gentle treatment with another person (GH – a woman wearing dark blue coveralls and white boots) and never had contact with AH again. For the gentle treatment, GH used a soft tone of voice and was careful during the same routine. The Human Approach Test was applied to measure the avoidance response of piglets to the approach of AH and an unfamiliar handler (UH) in a novel place, at 35 days and at 91 days after birth. Scores ranged from 1 (experimenter could touch piglets) to 5 (piglets escaped as soon as person moved). The UH was wearing white coveralls and white boots. Data were analyzed by t-test at day 35 and ANOVA and Tukey at day 91. At 35 days, piglets kept more distance from AH than from the UH (2.37±0.33 and 1.69±0.22 respectively, P=0.04), indicating that the piglets could recognize the aversive handler. At 91 days, piglets still kept more distance from AH than UH and GH (2.75±0.33; 1.31±0.15; 0.25±0,11 respectively, P<0.001), indicating that aversively treated piglets do not avoid an unknown handler, but still can remember the aversive handler with whom they had contact early in life. In conclusion, 35 and 91 days-old piglets show different avoidance responses to a human, according to the quality of handling received. Moreover, they recognize their handler and remember her after three weeks with no contact.